Do English noun phrases tend to minimize dependency distance?. Issue 2 (2nd April 2020) - Lu, Junyan; Liu, Haitao
ABSTRACT: Many studies have shown that, owing to the constraint of working memory capacity, language users prefer shorter dependency distances. However, these studies, which are all based on dependency distances in sentences or texts, leave the question unanswered: does noun phrase structure also demonstrate the tendency of dependency distance minimization? To answer this question, the article, based on a self-annotated English corpus, was carried out to probe the dependency distance in noun phrases between heads and their pre- and post- modifiers. The results show that the dependency distance between pre-modifiers and heads is much shorter than that between post-modifiers and heads. This finding suggests that noun phrases also show the tendency of dependency distance minimization, although they present a much longer mean dependency distance than sentences.